Streaming the beautiful game: exploring big tech's growing presence in the soccer industry - Alexis Fakataulavelua; Markus Lang; Jérémy Moulard (Frontiers Media S.A., 2023)
This study investigates the evolving role of major technology corporations-namely, Amazon, Apple, Microsoft, Facebook, Netflix, and Google-in the sports industry, with a specific focus on soccer. By employing a qualitative content analysis of media reports, scientific literature, and annual reports from 2000 to 2021, the research scrutinizes the varying approaches and investments of these tech giants in the domain of sports. The findings classify these companies into three distinct categories: (1) those actively securing broadcast rights for major competitions and leagues (Google, Facebook, Amazon); (2) those primarily producing and disseminating soccer documentaries (Netflix); and (3) those not directly engaging in media rights but advancing the technological aspects of clubs and leagues (Apple and Microsoft). This study underscores the escalating significance of Big Tech in reshaping the sports media landscape and calls for further research to comprehend the broader implications of their presence in sports broadcasting and fan engagement.